2020
DOI: 10.3390/ijms21165706
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Expansion and Expression Divergence of the Polygalacturonase Gene Family in Brassica oleracea

Abstract: Plant polygalacturonases (PGs) are closely related to cell-separation events during plant growth and development by degrading pectin. Identifying and investigating their diversification of evolution and expression could shed light on research on their function. We conducted sequence, molecular evolution, and gene expression analyses of PG genes in Brassica oleracea. Ninety-nine B. oleracea PGs (BoPGs) were identified and divided into seven clades through phylogenetic analysis. The exon/intron structures and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…Most IbPG proteins in our analysis possessed domain I and II, suggesting that these proteins may still be catalytically active but lost the ability to engage with the substrate that contain the ionic groups of the carboxylic acid groups. The members of Clade E were de cient in the domain III, and the similar results were observed in B. oleracea [33]. According to speculation, the members of Clade A and B include endo-PGs, the members of Clade C and D contain exo-PGs, Clade E members contain rhamno PGs, and Clade F members are neither exo-PGs nor endo-PGs, the variations in pectin components that each clade catalyzed may be shown by the evolutionary distinctions because of different types of PG enzyme have different substrates and products.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Most IbPG proteins in our analysis possessed domain I and II, suggesting that these proteins may still be catalytically active but lost the ability to engage with the substrate that contain the ionic groups of the carboxylic acid groups. The members of Clade E were de cient in the domain III, and the similar results were observed in B. oleracea [33]. According to speculation, the members of Clade A and B include endo-PGs, the members of Clade C and D contain exo-PGs, Clade E members contain rhamno PGs, and Clade F members are neither exo-PGs nor endo-PGs, the variations in pectin components that each clade catalyzed may be shown by the evolutionary distinctions because of different types of PG enzyme have different substrates and products.…”
Section: Discussionsupporting
confidence: 77%
“…The PG genes had been identi ed in many advanced plants recently [24]. For instance, there were 68, 46, 99, 75, 53, 62 PGs had been reported in A. thaliana, Oryza sativa, Brassica oleracea, Populus, Cucumis sativus and Citrullus lanatus, respectively [12,13,26,28,33]. The expression of PG genes played a vital role in alterations and modi cations of plant cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…What is important, they included cis-elements regulated by phytohormones and transcription factors, such as abscisic acid (ABRE), gibberellin (P-Box), auxin (TGA-element), methyl jasmonate (CGTCA, TGACG), and MYB binding site involved in drought-inducibility (MBS). Similar research was carried out in Brassica oleracea, and the hormone-response cis-elements were also found for MeJA (CGTCA), auxin (TGA-box and AuxRR-core), GA (GARE, P-box, TATC-box), salicylic acid (TCA-element), and abscisic acid (ABRE) [63].…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, they included cis-elements regulated by phytohormones and transcription factors such as abscisic acid (ABA; ABRE), GAs (P-Box), auxin (TGA-element), methyl jasmonate (MeJA; CGTCA, TGACG), and MYB binding sites involved in drought inducibility (MBS). Similar research was carried out in Brassica oleracea , and hormone-response cis-elements were found for MeJA (CGTCA), auxin (TGA-box and AuxRR-core), GA (GARE, P-box, TATC-box), salicylic acid (TCA-element), and ABA (ABRE) [ 69 ].…”
Section: Discussionmentioning
confidence: 59%